Research on a DC interconnection system based on a cascaded three-level converter for an island multi-energy microgrid - Liu, Xiaomin; Wang, Zheng; Liu, Shangke; Bai, Bin; Du, Xiangnan (Frontiers in Energy Research, 2024)
With the world’s transformation to low-carbon energy, island microgrids are developing rapidly because they can save energy and reduce carbon. Island multi-energy microgrids include photovoltaics, a double-fed fan, a battery energy storage system, and AC and DC loads. However, microgrids with high proportions of renewable energy have problems such as large power supply fluctuations and poor power quality. Connection to an AC power grid interconnection will greatly affect their reliability and stability. Firstly, a cascaded neutral point clamped three-level converter (C-NPC) DC interconnection system scheme is proposed. Secondly, the Island C-NPC mathematical models are established, and the flexible multi-mode control of island C-NPCs is proposed. Subsequently, corresponding additional control strategies for DC voltage sharing and AC current sharing among C-NPC modules are designed for the island multienergy microgrid to achieve reliable power supply. Finally, taking an island interconnection project on the east coast of China as a research object, a typical system operation test was performed to verify the good operational characteristics of the system. This research can promote the utilization of clean energy in island regional power grids, achieve carbon reduction, and promote global carbon neutrality.